A novel intervention for treating adults with ADHD using peripheral visual stimulation - Richter, Yael; Gordon, Carlos; Vainstein, Gabriel; Bublil-Mor, Carmel; Geisinger, Dario; Meital-Kfir, Noya; Elyoseph, Zohar (Frontiers in Psychiatry, 2023)
Objective: Stimulation of the peripheral visual field has been previously reported as beneficial for cognitive performance in ADHD. This study assesses the safety and efficacy of a novel intervention involving peripheral visual stimuli in managing attention deficit hyperactivity disorder (ADHD).Methods: One hundred and eight adults, 18-40 years old, with ADHD, were enrolled in a two-month openlabel study. The intervention (i.e., Neuro-glasses) consisted of standard eyeglasses with personalized peripheral visual stimuli embedded on the lenses. Participants were assessed at baseline and at the end of the study with self-report measures of ADHD symptoms (the Adult ADHD Self-Report Scale; ASRS), and executive functions (The Behavior Rating Inventory of Executive Function Adult Version; BRIEF-A). A computerized test of continuous performance (The Conners' Continuous Performance Test-3; CPT-3) was tested at baseline with standard eyeglasses and at the end of study using Neuro-glasses. The Clinical Global Impression-Improvement scale (CGI-I) was assessed at the intervention endpoint. Safety was monitored by documentation of adverse events.The efficacy analysis included 97 participants. Significant improvements were demonstrated in self-reported measures of inattentive symptoms (ASRS inattentive index; p = 0.037) and metacognitive functions concerning self-management and performance monitoring (BRIEF-A; p = 0.029). A continuousperformance test (CPT-3) indicated significantly improved detectability (d'; p = 0.027) and reduced commission error (p = 0.004), suggesting that the Neuro-glasses have positive effects on response inhibition. Sixty-two percent of the participants met the response criteria assessed by a clinician (CGI-I). No major adverse events were reported.Neuro-glasses may offer a safe and effective approach to managing adult ADHD. Results encourage future controlled efficacy studies to confirm current findings in adults and possibly children with ADHD.